Pengaruh Edukasi Terhadap Pengetahuan Pada Pasien Lansia Hipertensi di Rumah Sakit Umum Daerah Padang Pariaman - Naluri , Lisma; Nasif , Hansen; Sari, Yelly Oktavia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Hypertension is a prevalent chronic condition among the elderly, and improving patients' knowledge is a crucial factor in achieving successful therapy. This study aimed to evaluate the effect of educational interventions on knowledge among elderly hypertensive patients at Padang Pariaman General Hospital. A one-group pre-test post-test design was used involving 97 elderly participants who received education through pharmacist-led counseling sessions. Knowledge levels were assessed using the Hypertension Knowledge-Level Scale (HKLS). The Wilcoxon signed-rank test showed a significant improvement in knowledge after the intervention (p < 0.05). Before counseling, most participants had low knowledge, but this improved significantly post-education. The study concludes that structured educational interventions effectively enhance the knowledge of elderly hypertensive patients, and should be incorporated into routine pharmaceutical care.